Sistem Informasi Produksi Berbasis Web Pada Pt . Dharma Polimetal - Andri Firmansyah; Abdul Rohman (Teknik Informatika, Universitas Pelita Bangsa, 2018)
This research was conducted in order to find out how the application of the web-based production information system by using the first research method, namely the field method, which means that the writer directly collects data through interviews and direct observation, which aims to obtain accurate information, secondly uses the library method where data and information needed by the author is obtained from books and reading sources. It is expected that with the simple design of applications this activity on the company can become easier and production data can be real-time in its implementation and activities.